Barangay Council members' perception of the Barangay Integrated Development Approach for Nutrition Improvement of the Rural Poor (BIDANI) as a development approach used in selected villages of San Joaquin, Iloilo. - Pacit, Lucilyn
The study attempts to answer the following objectives: 1) To describe how the members of the barangay council understood BIDANI as a development approach; 2) To know how the members of the barangay council perceived the effectiveness of BIDANI as a development approach; 3) To know what are the problems encountered by the barangay council members in using BIDANI as an approach. , The five barangays in the municipality of San Joaquin were selected for the study. The barangay council members who served their respective barangays in 1991 were the respondents of this study. There were 32 of them all in all who were interviewed. The interview schedule was used to gather data. The result shows that nutrition as the major component of the BIDANI was not given due importance by the people. This is because they had their attention on the financing of the income-generating project which the BIDANI program staff was simultaneously implementing. Further, it was also found that the respondents were not able to understand well some aspect such as the goal of planning workshop and the role of the barangay captain in the BIDANI. The study revealed that BIDANI is effective in providing income-generating project and providing skills training to the barangay leaders. But as a process to link government and non-government agencies with members of barangay council it was not felt by the members. Lastly, the council members find minimal problems in using the BIDANI as a development approach. But in general, they have positive response toward BIDANI.